Efektivitas Sediaan Salep yang Mengandung Ekstrak Ikan Gabus (Channa striata) pada Proses Penyembuhan Luka Akut Stadium II Terbuka pada Tikus Jantan Galur Wistar - Andrie, Mohamad; Sihombing, Dies (Pharmaceutical Sciences and Research, 2018)
The snakehead (Channa striata) extract contains albumin (in its water phase) and omega-3 and omega-6 (in its oil phase) which have been proven to be effective in wound healing process. This research was aimed to determine wound healing effect of snakehead extract-containing ointment on 6 groups of male Wistar rats. The rat’s skin was wounded to produce acute stage II opened wound, the ointment was applied for sixteen days, and wound healing process was observed. The width of the wound was measured by using Macbiophotonic Image J program. The AUC results of each groups from smallest to largest were normal group (702.84% x day), negative group (749.56% x day), positive group (765.146% x day), water phase-containing ointment 10% group (795.146% x day), oil phase-containing ointment 10% (837.282% x day), and water-oil-phase combination ointment 10% (874.901% x day). The data were analyzed using One-Way ANOVA and Post-Hoc LSD test. The result of this research showed significant differences (p<0.05) between groups of water-oil phase combination of snakehead extract ointment with a negative control group. This research result showed that ointment containing water-oil phase combination of snakehead extract had wound healing effect on acute stage II opened wound.